Preparation, characterization and optimization for upgrading Leucaena leucocephala bark to biochar fuel with high energy yielding. (1st July 2016) - Anupam, Kumar; Sharma, Arvind Kumar; Lal, Priti Shivhare; Dutta, Suman; Maity, Sudip
Abstract: Biochar fuel (CH0.50 O0.19 N0.06 ) was prepared from Leucaena leucocephala bark (CH2.80 O0.53 N0.03 ) through the slow pyrolysis process adopting design of experiments technique. Modelling and optimization of the slow pyrolysis process was respectively carried out implementing five level central composite design and numerical technique under response surface methodology. Pyrolysis temperature and time were taken as independent parameters while biochar fuel yield, bulk density, higher heating value, energy density and energy yield were chosen as dependent parameters. The optimal pyrolysis temperature and time were estimated to be 367.47 °C and 135.38 min respectively. These optimum values of temperature and time gave biochar yield 47.29%, bulk density 319.73 kg/m 3, higher heating value 23.30 MJ/kg, energy density 1.21, and energy yield 56.55%. The developed quadratic models were checked using ANOVA (analysis of variance) technique for their validity and degree of fitness. The high values of 'Adequate precision', R 2 and its negligible difference with 'Adjusted R 2 ' as well as 'Predicted R 2 ' for each model indicated that the fitted empirical models can be used for prediction with reasonable precision. The quadratic models revealed strong interaction between pyrolysis temperature and time towards preparation of biochar fuel. It was further observed that desirability of pyrolysis temperature (0.91) is more than pyrolysis time (0.63). Comparison of Van Krevelen diagram of present biochar fuel with several other biochar fuels and coals showed that prepared biochar has better fuel properties in comparison to raw bark. Highlights: The first such report on conversion of Leucaena leucocephala bark to solid biochar fuel. Modelling and optimization of fuel preparation using response surface methodology. Fuel yield, bulk density, HHV (higher heating value), energy density and energy yield as key parameters. Significant interaction between pyrolysis parameters toward biochar fuel properties. Proximate composition, elemental analysis and Van Krevelen diagram of biochar fuel.